Pengaruh Tarif Iklan Terhadap Keputusan Berlangganan pada Siaran Radio Montini Manado - Manemba, Iranzo Lorenzo; Tampi, Johny R. E.; Mukuan, Danny D. S. (Sam Ratulangi University, 2019)
This study focuses on the influence of advertising rates on customer decisions with the location of research on Radio Montini as one of the audio media by concentrating on promoting advertising rates or prices. The aim is to find out the extent to which Radio Montini Manado broadcast advertising rates affect customer decisions. The method used is a quantitative method with a simple linear regression analysis approach. The results of this study indicate that Radio Montini advertising rates have a positive and significant effect on Radio Manado's Montini FM customer decisions because it is supported by research results in accordance with the results of the validity and reliability test, the significance test, and the SPSS test results. The effect of advertising rates or prices on customer decisions on Radio Montini is not necessarily the only factor that influences customer decisions, but there are also other factors that could not be examined. Based on the results of this study, it is known that advertising rates or prices have a very strong influence on customer decisions at Radio Montini.